2010
DOI: 10.1093/jjco/hyq053
|View full text |Cite
|
Sign up to set email alerts
|

High-dose-rate Intracavitary Brachytherapy Combined with External Beam Radiotherapy for Stage IIIb Adenocarcinoma of the Uterine Cervix in Japan: A Multi-Institutional Study of Japanese Society of Therapeutic Radiology and Oncology 2006-2007 (Study of JASTRO 2006-2007)

Abstract: The 5-year overall survival rate of stage IIIb adenocarcinoma of the uterine cervix in this retrospective questionnaire survey was 20.2%. The optimal T-BED(10) and evident prognostic factors were not clear from this questionnaire survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 9 publications
1
27
2
Order By: Relevance
“…29 However, ADC has been shown to be less sensitive to radiotherapy compared with SCC. 23,28,34,35 These factors are likely to contribute to the differences observed in survival among histological types of cervical cancer in Ghana.…”
Section: Resultsmentioning
confidence: 99%
“…29 However, ADC has been shown to be less sensitive to radiotherapy compared with SCC. 23,28,34,35 These factors are likely to contribute to the differences observed in survival among histological types of cervical cancer in Ghana.…”
Section: Resultsmentioning
confidence: 99%
“…According to a previous study, RT was less effective compared to surgery in patients with AC (13). Recently, Niibe et al (14) reported that the 5-year OS for stage IIIB patients with AC treated with high-dose intracavitary brachytherapy combined with external beam radiotherapy was 20.2%. The 5-year OS for stage IIIB patients with SCC has been reported to be 47.2–55.2% in Japan (1719).…”
Section: Discussionmentioning
confidence: 99%
“…18,39 In addition, the subset analysis of a cohort study suggested that patients with GAS seemed significantly more resistant to radiotherapy compared with those with UEA. 40 To achieve better oncologic outcome for locally advanced patients with aggressive cervical cancer, such as GAS, various multidisciplinary therapeutic strategies incorporating cisplatin-based CCRT and molecular targeting therapy have been evaluated.…”
Section: Figurementioning
confidence: 99%
“…Recent literature suggested that CCRT with weekly CDDP was less effective for patients with uterine cervical non-SCC than for those with SCC. 18,19 Therefore, half of all Japanese gynecologic oncologists chose RH for stage IIB patients with non-SCC, despite the fact that only a third selected RH for those with SCC. 20 Although an international collaborative meta-analysis of neoadjuvant chemotherapy (NAC) also reported that NAC reduced the need of adjuvant radiotherapy by decreasing pathological risk factors and distant metastasis, but failed to improve survival compared with RH without NAC, 21 Neoadjuvant chemotherapy followed by RH is also permitted as one of the optional strategies for stages IB2, IIA2, and IIB patients with cervical cancer in Japan.…”
mentioning
confidence: 99%